2007
DOI: 10.1073/pnas.0700548104
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-conjugating enzyme Ubc13 is a critical component of TNF receptor-associated factor (TRAF)-mediated inflammatory responses

Abstract: Ubc13 is a ubiquitin-conjugating enzyme responsible for noncanonical ubiquitination of TNF receptor-associated factor (TRAF)-family adapter proteins involved in Toll-like receptor and TNFfamily cytokine receptor signaling, which are regulators of innate immunity. Gene ablation was used to study the function of Ubc13 in mice. Whereas homozygous ubc13 gene disruption resulted in embryonic lethality, heterozygous ubc13 ؉/؊ mice appeared normal, without alterations in immune cell populations. Haploinsufficient ubc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 33 publications
2
104
0
Order By: Relevance
“…In response to TNF-a, UBC13 þ /À macrophages and splenocytes showed blunted activation of NF-kB, JNK, and p38 signaling pathways. 71 In contrast, UBC13 À/À MEFs displayed no alteration in these signaling pathways relative to wild-type MEFs. 72 Although these discrepancies may be attributable to cell type-specific differences, experiments with UBC13 null cells suggest that other E2 enzymes may substitute for UBC13 in TNF-a signaling pathways.…”
Section: Dr Signaling Is Regulated By Ubiquitinationmentioning
confidence: 97%
“…In response to TNF-a, UBC13 þ /À macrophages and splenocytes showed blunted activation of NF-kB, JNK, and p38 signaling pathways. 71 In contrast, UBC13 À/À MEFs displayed no alteration in these signaling pathways relative to wild-type MEFs. 72 Although these discrepancies may be attributable to cell type-specific differences, experiments with UBC13 null cells suggest that other E2 enzymes may substitute for UBC13 in TNF-a signaling pathways.…”
Section: Dr Signaling Is Regulated By Ubiquitinationmentioning
confidence: 97%
“…Ubc13 is also required for TRAF6 poly-ubiquitination and IKK activation in vivo, as spleen lysates from LPS-treated mice heterozygous for Ubc13 show lower poly-ubiquitination of TRAF6 than isolates from wild-type mice. IkBa degradation in response to LPS is also impaired in macrophages and splenocytes from Ubc13 +/-mice [43]. In contrast, Yamamoto et al revealed that Ubc13-deficient murine embryonic fibroblasts show normal activation of NF-kB in response to IL-1, whereas JNK activation is impaired [44].…”
Section: Il-1r and Tlr-4 Signaling To Nf-kbmentioning
confidence: 98%
“…Finally, TAB2, TAB3 and IKKg also become K63-poly-ubiquitinated by TRAF6 [22, 47 -49]. A role for oligomerization of TRAF6 in enhancing its ubiquitinating activity has also been postulated [39,42,43]. In fact, TRAF-interacting protein with a forkhead-associated domain (TIFA) was found to interact with TRAF6, thereby inducing TRAF6 oligomerization and enhancing TRAF6 ubiquitinating activity [50].…”
Section: Il-1r and Tlr-4 Signaling To Nf-kbmentioning
confidence: 99%
See 1 more Smart Citation
“…8a) in LRRC19 and TRAF2 or TRAF6 co-expressing HEK293T cells. As TRAF6 and TRAF2 could be ubiquitinated in the process of signal transduction [26][27][28] , we hypothesized that the interaction of LRRC19 and TRAF6 or TRAF2 could affect the ubiquitination of TRAF6 and TRAF2. While the cells were transfected using Myc-tagged TRAF2 with control empty plasmid, degradation of TRAF2 could be observed (Fig.…”
Section: Lrrc19 Promotes Expression Of Antimicrobial Substancesmentioning
confidence: 99%